Strategi Pemasaran Produk Tabungan Easy Wadiah Dalam Meningkatkan Kepuasaan Nasabah di Bank Syariah Indonesia : Pendekatan Systematic Literature Review (SLR) - Sam’udin, Sam’udin; Fasa, Muhammad Iqbal (LPPM Universitas Islam 45, 2024)
This reseacrh aims to determine the marketing strategy of easy wadiah savings products in increasing customer satisfaction of Islamic banks through a systematic literature review approach. This research uses a qualitative research concept that aims to explain and analyze the marketing strategy of easy wadiah savings products. Systematic literature review in this qualitative research integrates and analyzes various relevant literature to identify effective strategies, challenges, and opportunities in marketing Islamic savings, especially in Indonesia which has its own cultural characteristics and religious preferences. The data source used is secondary data derived from various relevant research journals. The data collection technique is done by literature study. The results of the discussion of the systematic literature review showed that wadiah as a deposit from one party to another, both individuals and legal entities that must be maintained and returned whenever the depositor wishes. The marketing strategy used to market easy wadiah savings products used by Bank Syariah Indonesia in marketing products, especially wadiah savings, can be by analyzing the marketing mix which consists of four elements, namely product strategy, price strategy, place strategy and promotion strategy. Based on the results of this study, the suggestions that can be given are that BSI products, especially easy wadiah savings products to the public and their advantages as widely as possible by increasing promotion through social media and BSI in the future can further improve quality, one of which is improving services, facilities and infrastructure and management in achieving the vision and mission of Islamic banks.